2018
DOI: 10.3390/cancers10040099
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options for Paediatric Anaplastic Large Cell Lymphoma (ALCL): Current Standard and beyond

Abstract: Anaplastic Lymphoma Kinase (ALK)-positive Anaplastic Large Cell Lymphoma (ALCL), remains one of the most curable cancers in the paediatric setting; multi-agent chemotherapy cures approximately 65–90% of patients. Over the last two decades, major efforts have focused on improving the survival rate by intensification of combination chemotherapy regimens and employing stem cell transplantation for chemotherapy-resistant patients. More recently, several new and ‘renewed’ agents have offered the opportunity for a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 91 publications
0
78
0
3
Order By: Relevance
“…As ALCL was not recognised as a distinct entity until the early 1980s, it would have been treated as a NHL. Indeed, retrospective studies have shown that a number of ALCL cases were treated within both B‐ or T‐cell NHL trials (extensively reviewed in Prokoph et al , ). The European Inter‐group for Childhood NHL (EICNHL) led the first international ALCL‐specific clinical trial, initiated in 1999, for patients under the age of 22 years: ALCL99 (NCT00006455) (Attarbaschi et al , ; Mori et al , ).…”
Section: The History Of Alclmentioning
confidence: 99%
See 4 more Smart Citations
“…As ALCL was not recognised as a distinct entity until the early 1980s, it would have been treated as a NHL. Indeed, retrospective studies have shown that a number of ALCL cases were treated within both B‐ or T‐cell NHL trials (extensively reviewed in Prokoph et al , ). The European Inter‐group for Childhood NHL (EICNHL) led the first international ALCL‐specific clinical trial, initiated in 1999, for patients under the age of 22 years: ALCL99 (NCT00006455) (Attarbaschi et al , ; Mori et al , ).…”
Section: The History Of Alclmentioning
confidence: 99%
“…Instead, a number of retrospective studies by European and Japanese groups assessed the success with which small cohorts of patients had been treated, using either allogeneic or autologous stem cell transplantation (SCT). There is some evidence to show that allogeneic SCT yields better outcomes for relapse patients, yet there is no consensus on this, nor on the type of conditioning which should be used, although radiotherapy seems to be the most common option (Reviewed in Prokoph et al , ). There is also limited data concerning the best treatment options for refractory patients who do not respond to standard chemotherapy, although some of the more recent trials have shown promise.…”
Section: The History Of Alclmentioning
confidence: 99%
See 3 more Smart Citations